2016
DOI: 10.1186/s11671-016-1312-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Photoluminescence Study of Large-Area Ordered and Size-Controlled GeSi Multi-quantum-well Nanopillar Arrays

Abstract: Large-area ordered GeSi multi-quantum-well nanopillar array (MQW-NPA) samples with different nanopillar lateral sizes (270, 120, and 70 nm) are fabricated by a cost-effective and scalable dry-etching process in combination with nanosphere lithography technique. A significant enhancement in photoluminescence (PL) intensity has been observed in the GeSi MQW-NPA samples compared with the as-grown GeSi MQW one. Nanopillar samples with different lateral sizes show different enhancements in PL intensity. The enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…While we included PL data for series 2 obtained from a different measurement setup in the Supplemental Material [27], we restrict the following results and discussion to data obtained from series 3. An increase in PL signal intensity in structured nanocolumn samples compared to the unstructured samples has been observed previously [49] and was attributed to an increase in absorption of the incident light due to the antireflective properties of the patterned surface as well as an increase in the effective penetration depth of the incident laser light.…”
Section: Resultssupporting
confidence: 70%
“…While we included PL data for series 2 obtained from a different measurement setup in the Supplemental Material [27], we restrict the following results and discussion to data obtained from series 3. An increase in PL signal intensity in structured nanocolumn samples compared to the unstructured samples has been observed previously [49] and was attributed to an increase in absorption of the incident light due to the antireflective properties of the patterned surface as well as an increase in the effective penetration depth of the incident laser light.…”
Section: Resultssupporting
confidence: 70%
“…where Ω is the damping factor, ρ [k+1] (z) is the damped charge distribution which will be used to replace ρ [k+1] (z) in equation (19) at iteration step (k + 1). The charge distribution of each step will be damped by adding a part of the results of its history from the last iteration.…”
Section: Iteration Processmentioning
confidence: 99%
“…So far, CSE in GeSi QWs has not been sufficiently investigated. Jiang et al found that the wavelength of the peak optical gain was related to the carrier density which indicates a shift in energy level was introduced by an extra carrier [19]. Pizzi et al ruled out the attempt of doping in the barriers because of the severe electrostatic potential that will break the confinement potential [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polystyrene (PS) nanospheres have been attracting great attention from several research fields due to their ability for fabricating novel nanomaterials and nanostructures, such as ordered nanowire arrays [ 1 3 ], nanopillar arrays [ 4 , 5 ], nanohole arrays [ 6 , 7 ], nanodot arrays [ 8 ], core/shell composite materials [ 9 , 10 ], nanomesh [ 11 , 12 ], and magnetic quantum dots [ 13 ]. Particularly, nanosphere lithography has been one of the most popular research hotspots in designing the ordered nanostructure arrays since it takes the advantages of simpler process and lower cost.…”
Section: Introductionmentioning
confidence: 99%